2021
DOI: 10.1093/cid/ciab715
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Hospital Administration of Remdesivir During a Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Outbreak in a Skilled Nursing Facility

Abstract: Completion of a 5-day course of remdesivir was associated with approximately 17fold increased odds of survival among a sample of 54 nursing home residents with SARS-CoV-2 infection during the course of an outbreak from October to December, 2020. Remdesivir was well-tolerated; administration was logistically feasible in a pre-hospital environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Moreover, the final results of ACCT-1 and WHO solidarity randomized clinical trials suggest that remdesivir offers no substantial benefit to ventilated COVID-19 patients but aids in reducing death or the need for ventilation in other hospital cases, especially in patients requiring low-flow supplemental oxygen [32,37,38]. Additionally, multiple observational studies, but not all, have shown an association with remdesivir use in hospitalized patients and reduced mortality [35,36,[39][40][41][42][43][44][45][46][47]. Finally, a systematic review and individual patient data meta-analysis of eight randomized clinical trials (RCTs) consisting of 10,480 patients hospitalized with COVID-19 found a significant reduction in mortality with remdesivir use compared to non-use (OR 0.88; 95% CI, 0.78 to 1.00; p = 0.045) [38].…”
Section: Remdesivir's Role In the Treatment Of Covid-19 In Hospitaliz...mentioning
confidence: 99%
“…Moreover, the final results of ACCT-1 and WHO solidarity randomized clinical trials suggest that remdesivir offers no substantial benefit to ventilated COVID-19 patients but aids in reducing death or the need for ventilation in other hospital cases, especially in patients requiring low-flow supplemental oxygen [32,37,38]. Additionally, multiple observational studies, but not all, have shown an association with remdesivir use in hospitalized patients and reduced mortality [35,36,[39][40][41][42][43][44][45][46][47]. Finally, a systematic review and individual patient data meta-analysis of eight randomized clinical trials (RCTs) consisting of 10,480 patients hospitalized with COVID-19 found a significant reduction in mortality with remdesivir use compared to non-use (OR 0.88; 95% CI, 0.78 to 1.00; p = 0.045) [38].…”
Section: Remdesivir's Role In the Treatment Of Covid-19 In Hospitaliz...mentioning
confidence: 99%